USHUL DAN FURU’ DALAM PERSPEKTIF MAQASID AL-SHARI’AH: REKONSTRUKSI HIERARKI KEBUTUHAN DARURIYYAH, HAJJIYAH DAN TAHSINIYYAH - Ahmad Sayyidiman Hamidalloh; M. Zainuddin Ali; Ahmad Fika Assyidiq; Muhammad Arosyiddin (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2026)
This study aims to analyze the relationship between ushul and furu' from the perspective of maqasid al-shari'ah, and reconstruct the hierarchy of human needs that include daruriyyah, hajjiyyah, and tahsiniyyah as instruments in determining the priority of public welfare. The background of this research is based on the increasing complexity of contemporary social issues that cannot be fully answered through a textual and formalistic fiqh approach. This study uses a qualitative approach with a library research method, with data sources in the form of relevant scientific articles. Data analysis techniques are carried out through content analysis with a descriptive-analytical and conceptual approach. The results of the study indicate that the relationship between ushul and furu' is dialectical and interdependent, not dichotomous as generally understood. Usul functions as a normative and methodological basis, while furu' is a form of actualization of law in practical life. In this context, maqasid al-shari'ah acts as an integrative framework that connects the two and directs the orientation of law towards public welfare. Furthermore, the concept of the hierarchy of human needs within the maq??id (the principles of law) needs to be dynamically reconstructed, as modern reality has seen shifts in the categories of needs due to social and technological developments. The implications of these findings suggest that social fiqh needs to be developed through a more substantive, adaptive, and contextual approach to the maq??id (the principles of law) so that Islamic law remains relevant in addressing the challenges of the times.